THE INFLUENCE OF MACROECONOMIC INDICATORS ON THE PROFITABILITY OF CONVENTIONAL AND ISLAMIC BANKS: AN ISLAMIC ECONOMIC LAW PERSPECTIVE - alfiyan, fri haendid; Cahya Lestari, Kurnia; Nasyah Agus Syaputra, Muhammad (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze the influence of macroeconomic indicators, namely inflation, exchange rate, and interest rate (BI Rate), on the profitability of conventional and Islamic banks in Indonesia, viewed through the lens of Islamic economic law. Using a quantitative approach with secondary data from financial reports and macroeconomic sources, the study applies t-tests, F-tests, and multiple linear regression analysis via SPSS 26. The findings reveal that only the BI Rate significantly affects the profitability (ROA) of conventional banks, while all macroeconomic variables show no significant impact on Islamic banks. From the perspective of Islamic economic law, this outcome affirms the inherent stability of Islamic banking principles, which emphasize fairness, risk-sharing, and the prohibition of riba. These principles help insulate Islamic banks from macroeconomic volatility. The results underscore the strategic importance of strengthening the Islamic banking system and integrating sharia-based monetary policies to support a more resilient and equitable financial system in the long term.